Axial and flexural performances of columns restored after severe damage. (December 2021) - Hwang, Seung-Hyeon; Yang, Keun-Hyeok; Choi, Yong-Soo; Kwon, Seung-Jun
Abstract: This study presents the structural potentials of an entire restoration technique proposed for upgrading the strength and ductility of severely damaged non-seismic columns. Three columns were prepared under concentric axial loads to examine the axial load–axial strain relationship of restored columns. Additionally, five columns subjected to a constant axial load and cyclic lateral loads were prepared to ascertain the seismic behavior of the restored columns. To simulate the entire restoration of damaged columns, non-seismic columns were initially tested up to their peak axial capacity or 80% of the flexural strength on the post-peak performance; the longitudinal and transverse reinforcing bars and concrete were then reconstructed after total removal from the initially damaged columns. The test results showed that the axial load–axial strain and lateral load–lateral displacement relationships of the restored columns exhibited pre-peak behavior that was quite similar to that of the initial non-seismic columns, whereas the slope at the post-peak branches significantly slowed down for the former columns in comparison to the latter ones. Thus, the axial and flexural strengths of the restored columns could be conservatively assessed by the procedure recommended in the ACI 318-19 provision. The restored columns displayed axial ductility and flexural displacement ductility ratios comparable to those obtained in columns strengthened using the reinforced concrete (RC) jacket with seismic details that were developed using an approach similar to the proposed restoration technique. Thus, the proposed technique shows significant potential in enhancing the seismic performance of severely damaged non-seismic columns by providing confinement to concrete cores and preventing premature buckling of longitudinal reinforcements. Highlights: We develop an original entire restoration technique for damaged RC columns. Reasonable rearrangement of seismic reinforcements is proposed for restoration. This study presents valuable comparisons on ductile indices of columns. We verified the significance of ductile parameters in entirely restored columns.